Solar energy components in cotton and safflower crops - RAJEGOWDA, M. B. (MAUSAM, 1991)
Solar energy components at different phenophases of cotton (Gossypium hirsutum) and safflower (Carthanus tinctorius) crops were measured. The percentage of different components are calculated. Solar energy utilisation component is found maximum during flowering stage in cotton and during seed setting stage in safflower. The albedo is constant till the flowering stage and gradually increases reaching a maximum at the boll development stage and later decreases gradually in the cotton crop. In the case of safflower, the albedo gra dually increases till the seed setting stage is attained and decreases. The transmitted component first decreases and then increases in both the crops.